Attachment and dissociation as mediators of the link between childhood trauma and psychotic experiences. (27th June 2017) - Pearce, Josie; Simpson, Jane; Berry, Katherine; Bucci, Sandra; Moskowitz, Andrew; Varese, Filippo
Abstract : Exposure to childhood trauma has been implicated in the development of paranoia and hearing voices, but the mechanisms responsible for these associations remain unclear. Understanding these mechanisms is essential for ensuring that targeted interventions can be developed to better support people experiencing distress associated with paranoia and voices. Recent models have proposed that dissociation may be a mechanism specifically involved in the development of voices and insecure attachment in the development of paranoia. Recent theoretical proposals have added to this and argued that fearful attachment could also lead to increased vulnerability for voices. This study was the first to examine whether dissociation and insecure attachment styles mediated the relationship between childhood trauma and these psychotic experiences. One hundred and twelve participants experiencing clinical levels of psychosis completed measures of dissociation, childhood trauma, attachment, voices, and paranoia. Results revealed positive associations between fearful (but not dismissive and anxious) attachment, dissociation, trauma, and psychotic experiences. Mediation analyses indicated that dissociation, but not fearful attachment, significantly mediated the relationship between trauma and voices. Conversely, both dissociation and fearful attachment significantly mediated the relationship between trauma and paranoia. The findings suggest that insecure attachment might be more strongly related to paranoia than hallucinations and suggest that fearful attachment may be a more promising mechanism to explain this relationship. Furthermore, the findings suggest that the impact of dissociation on psychotic experiences may extend to paranoia. Future research is required to replicate these findings using interview‐based attachment measures.